Islam and the Western philosophy of knowledge - Ali, Muhammad Mumtaz (Pelanduk, 1994)
Islam and the Western Philosophy of Knowledge, a humble contribution to the contemporary debate on the need for a new epistemology, examines some important issues of the philosphy of knowledge from both the Islamic and Western perspectives.